Which Sternotomy Closure Method (Orthopaedic Wire or Suture) Is Recommended in Large Breed Dogs Undergoing a Median Sternotomy? - Howes, Charlotte; Chanoit, Guillaume (Veterinary Evidence, 2018)
PICO question Which sternotomy closure method (orthopaedic wire or suture) is recommended in large breed dogs undergoing a median sternotomy? Clinical bottom line The literature search revealed no clinical studies on large breed dogs comparing the clinical outcomes following either orthopaedic wire or suture sternotomy closure methods. Post-mortem studies on large breed dogs suggest that sutures are as suitable as orthopaedic wires for sternal closure with regards to their biomechanical properties. There is insufficient clinical evidence to make a recommendation that sutures be used in large breeds of dog.